The question of space in Carl Schmitt. (June 2015) - Minca, Claudio; Rowan, Rory
In this paper we present an analysis of the German legal and political theorist Carl Schmitt as a spatial thinker whose work contains many elements relevant to the concerns of political geography. In examining his fundamental concern with how to ground modern political order without theological foundation, we identify a conceptual matrix between space, political order and conflict that underpins his thought. Charting the development of his spatial theory across his work, we focus on two key spatial moments from immediately before and after the Second World War: first, his theory of Großraum ('greater space') order as a reformulation of global order after the eclipse of the state and its complicated entanglements with Nazi spatial thinking and expansionism in eastern Europe; second, his notion of nomos, developed after the war to embrace both a geo-elemental spatial ontology and an account of the rise and fall of Eurocentric global order. We conclude by noting Schmitt's failure to move beyond an understanding of order grounded on spatial division and his increasing retreat into eschatological fantasy as global spatio-political relations became increasingly more complex in the late 20th century.